Satellite network underlying LMS for coverage and performance enhancement - Najdet Nasret Coran, Ali; Shakor Mahmood, Zuhair; B. Salih, Arshad (International Journal of Engineering and Technology, 2019)
Facilitating the process of learning in real life by employing of available communication techniques (mostly by internet) is termed as E-learning. With time advance, education of today developed with more publicity so then, students from remote venues are get-ting access to their course of interest even though far once of courses, with such capability of education, students start searching the interested courses and teaching style as well, that raised a new concern to be applied into classical methods of educations. Rural and remote regions can be provided with quality education through E-learning; the same is proposed in this article to connect stu-dent with remote lecturers and tutors effectively.Â Â Â